Analysis of the immunization data recorded in children's health books - Simone Mourão Abud; Maria Aparecida Munhoz Gaíva (Universidade Federal de Goias, 2014)
The objective of this study was to analyze the records of immunization data in the health books of children one year old and younger. This descriptive, cross-sectional study was performed in family health units of Cuiabá/MT, with 950 health books, from which data were collected in the second stage of the 2011 poliomyelitis immunization campaign. Of all health books, 60.3% (573) presented the complete immunization schedule while 39.7% (377) showed some delays. No associations were found between mothers' variables and immunization schedule. It was observed that over 92% of the information was filled out, such as the immunization date, lot number and the signature of the health care professional. Furthermore, 98.7% (938) of health books reported the dates of the next doses. The study showed that although most health books presented an up-to-date immunization situation, the delay rate is concerning as immunizations are mandatory in children's first year of life. Descriptors: Child Health; Pediatric Nursing; Primary Health Care; Immunization.